Imagining an inclusive economy: The role of SMEs and digital payment in elevating economic equality - Kiki Khoifin; Dzakiyy Hadiyan Achyar (Asian Development Bank Institute (ADBI), 2023)
Central to this study are small and medium enterprises (SMEs) and mainstreaming digital features that transform access to finance in imagining an inclusive economy. Underlining the advancement in technology, especially in the context of a digital payment system, perpetuates the financial-economic rationale as a means of financial inclusion. Nevertheless, the implementation remains a long-standing challenge, most notably in developing economies. Thus, this study assesses SMEs' efforts and digital payment in elevating economic equality in Southeast Asia. The panel data approach, as the econometric technique, is employed to examine the relationship between SMEs' contribution to the gross domestic product (GDP), digital payment, and the existing inequality proxied by the Gini coefficient. This study concludes with two core findings: (1) SMEs significantly help reduce inequality within the economy; (2) digital payment, as a digital transformation, narrows the inequality gap within Southeast Asian countries. Concluding remarks, recommendations, and suggestions for future research are presented.
Keywords: E42; I31; O53; 330; SMEs; digital payment; economic inequality; Southeast Asia